Analysis of the Contribution of Historical Empathy to the Achievement Student Profile of Pancasila - Susanto, Heri; Sariyatun, Sariyatun; Djono, Djono; Fathurrahman, Fathurrahman (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
The student profile of Pancasila is a critical concept which contains essential aspects of Indonesian human personality. One of these personality aspects is empathy for fellow citizens and humans. This study aims to analyze the influence of students’ historical empathy preferences with elements of the student profile of Pancasila and the suitability of historical empathy aspects to achieve a student profile of Pancasila. This study uses a quantitative method to determine the effect of historical empathy on the achievement of Pancasila’s student profile. Data collection was carried out using a questionnaire referring to aspects of historical empathy and elements/sub-elements of the student profile of Pancasila. The results showed a significant influence on the achievement of historical empathy with the achievement of the student profile of Pancasila. Using three elements/sub-elements in this analysis shows the empirical contribution of the historical empathy aspect in achieving the student profile of Pancasila. The study results confirm that historical empathy can be used to achieve Pancasila’s student profile.